Protocol to identify the ligand binding site of Mincle using NMR spectroscopy - Atsushi Furukawa; Hiroyuki Kumeta; Takashi Saitoh; Katsumi Maenaka (STAR Protocols, 2024)
Summary: Mincle (macrophage-inducible C-type lectin, CLEC4E) is a C-type lectin immune-stimulatory receptor that can be targeted for inducing potent adjuvant effects. Mincle can recognize trehalose dimycolate and related glycolipids. Here, we present a protocol to identify the ligand binding mode of Mincle. We describe steps for preparing labeled Mincle ectodomain, data acquisition, and analysis of nuclear magnetic resonance experiments using non-detergent sulfobetaine-195. This protocol can be applied to other protein-ligand interactions that have aggregation problems for complex formation.For complete details on the use and execution of this protocol, please refer to Furukawa et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.